2022
DOI: 10.3390/ijerph19137871
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19 Stress and COVID-19 Vaccination Acceptance among Adolescents in Ghana

Abstract: Coronavirus disease 2019 (COVID-19) continues to ravage world economies, and with its recent mutations, countries worldwide are finding ways of ramping up their vaccination programmes. This cross-sectional design study, therefore, examined the predictors of COVID-19 stress and COVID-19 vaccination acceptance among adolescents in Ghana. A total of 817 participants were conveniently selected to respond to measures on fear of COVID-19, perceived stigma from COVID-19, self-stigma from COVID-19, believing COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Therefore, readers should exercise caution in overly extending the findings. Lastly, the coronavirus (COVID-19) pandemic may have influenced the results as previous studies have associated COVID-19 variables with mental health conditions [ 70 , 71 , 72 , 73 , 74 , 75 ]. That is, COVID-19 has been reported to have deteriorated people’s mental health via increased job stress or problematic use of social media, smartphones, and other digital devices [ 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, readers should exercise caution in overly extending the findings. Lastly, the coronavirus (COVID-19) pandemic may have influenced the results as previous studies have associated COVID-19 variables with mental health conditions [ 70 , 71 , 72 , 73 , 74 , 75 ]. That is, COVID-19 has been reported to have deteriorated people’s mental health via increased job stress or problematic use of social media, smartphones, and other digital devices [ 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…One cross-sectional study showed that stress faced by adolescents may lead to physical and mental health challenges and that COVID-19 may lead to the deterioration of adolescents' mental health ( 5 ). During the COVID-19 pandemic, the incidence of mental health symptoms such as depression, anxiety, and insomnia was higher than that before the outbreak ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the quest to understand and improve the COVID-19 vaccination drive, some researchers assume that some COVID-19-related variables—such as COVID-19 stress, fear of COVID-19, perceived stigma from COVID-19, self-stigma from COVID-19, and believing COVID-19 information—may be helpful in this regard [ 16 , 17 , 18 ]. For instance, a study by Adjaottor et al [ 19 ] reported that believing COVID-19 information, danger and contamination fears, and traumatic stress (subscales of COVID-19 stress) were significant predictors of COVID-19 vaccination acceptance but not fear of COVID-19, perceived stigma from COVID-19, self-stigma from COVID-19, and COVID-19 infection prevention behaviours. Other researchers have reported interesting findings after examining the association between COVID-19-related variables and COVID-19 vaccination, taking into consideration sex, migration status, and others [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study among the Hungarian population revealed that more participants were willing to receive a COVID-19 vaccine compared to seasonal influenza, even after grouping participants based on demographic data or perceived financial status [ 37 ]. Other studies provided different reasons and factors influencing COVID-19 vaccination [ 19 , 38 , 39 , 40 ]. Taking these studies into consideration, there will be a need for more studies examining the intention of receiving different vaccines and attitudes towards those vaccines and the vaccination drive.…”
Section: Introductionmentioning
confidence: 99%